PERLINDUNGAN HUKUM DAN TANGGUNG JAWAB PELAKU USAHA ATAS HILANGNYA PAKET DALAM JASA LAYANAN PENGIRIMAN BARANG MELALUI PT JNE WILAYAH TANGERANG - Witiyas, Bernadeth Filia; Anggraini, A.M Tri (Fakultas Hukum Universitas Tarumanagara, 2021)
People at this time often carry out activities to send goods from one place to another using freight forwarding services and in Indonesia one of the most widely used goods delivery service companies is PT JNE.As time goes by, the relationship between PT JNE and the sender or recipient often finds problems such as lost packages of goods.In this paper, there are problems that will be discussed, namely how consumer protection as the use of goods delivery services according to the Consumer Protection Law and regulations related to the sector and how is the responsibility of PT JNE regarding the loss of packages due to negligence in the delivery process according to the Protection Law. Consumers and regulations relating to other sectors. The research method used in this thesis is normative legal research. The results of the author's research are the protection of consumers as users of goods delivery services and the responsibility of PT JNE is contained in the Consumer Protection Act, the Civil Code, the Commercial Code, and the Postal Law.The author hopes that business actors maintain the trust of consumers who have chosen to use or use products that are produced / produced obediently and are subject to applicable statutory regulations so that there is no incident where consumers are disadvantaged due to using their goods or services. Then, the government needs to provide counseling, provisioning and outreach for consumers and business actors so that they are more aware of their rights and obligations.